BUDAYA TRI HITA KARANA SEBAGAI PEMODERASI PENGARUH GOOD CORPORATE GOVERNANCE PADA KINERJA LPD KABUPATEN BADUNG - Sujana, I Ketut; Suardikha, I Made Sadha; Vinensya, Ni Luh Putu Pitayani (Buletin Studi Ekonomi; VOL.27.NO.1.FEBRUARI 2022DO - 10.24843/BSE.2022.v27.i01.p03, 2022)
This study aims to obtain evidence of the influence of Good Corporate Governance (GCG) on performance with Tri Hita Karana (THK) culture as a moderating variable. This research was conducted at the Village Credit Institution (LPD) of Badung Regency. The research sample was determined by the saturated sample method, as many as 122 respondents from LPD heads in Badung Regency. Data collection was done by using the questionnaire method. The hypothesis was tested by using the technique of Moderating Regression Analysis (MRA). The results showed that GCG had a positive effect on performance. The THK culture is not able to moderate the influence of GCG on performance. The more the application of GCG principles increases, the more performance occurs and perhaps THK values ??have been implemented in LPD operations but have not been able to significantly strengthen the influence of GCG principles on performance. This research can be used as a reference for the government and traditional villages, especially LPD managers and traditional village officials in carrying out their duties.